2019
DOI: 10.32098/mltj.04.2019.05
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport After Patellar Tendon Rupture:a Systematic Review

Abstract: Background. Patellar tendon rupture is a rare and disabling injury that may occur during sport practice and is considered as the 4 th stage of the Blazina's classification of jumper's knee. Return to sport after patellar tendon rupture has not been clearly assessed. Methods. Medical databases were screened, and article research extended from 1980 to April 2019. The inclusion criteria were report of more than 2 cases of isolated and complete uni-or bilateral patellar tendon rupture, patients over 18. Studies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Reported rates of return to sports in the current literature vary from 52% to 100%, although these studies are limited in size, ranging from 4 to 66 patients. 9 The return to activity rate of 75.8% found in this present study of 483 patients thus contributes to the ability of surgeons to more confidently counsel young and active patients on reasonable expectations of returning to their previous level of activity and highlights that although rerupture rates were low, a significant proportion (24.2%) of patients were unable to return to their full previous level of activity. Even though the lower return to full activity rate of revision repairs (8/15; 53.3%) was not statistically different from that of primary cases ( P = .145), it is possible that a larger number of revision cases would be needed to reveal a statistically significant difference.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Reported rates of return to sports in the current literature vary from 52% to 100%, although these studies are limited in size, ranging from 4 to 66 patients. 9 The return to activity rate of 75.8% found in this present study of 483 patients thus contributes to the ability of surgeons to more confidently counsel young and active patients on reasonable expectations of returning to their previous level of activity and highlights that although rerupture rates were low, a significant proportion (24.2%) of patients were unable to return to their full previous level of activity. Even though the lower return to full activity rate of revision repairs (8/15; 53.3%) was not statistically different from that of primary cases ( P = .145), it is possible that a larger number of revision cases would be needed to reveal a statistically significant difference.…”
Section: Discussionmentioning
confidence: 52%
“…2 A systematic review of return to sports after patellar tendon rupture identified a range in reported return rates from 52% to 100%, noting a low level of evidence among the studies included. 9…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in knee strength or vertical jump performances in basketball players should more accurately be considered a consequence of PT or of another knee joint injury than a risk factor [ 15 , 16 ]. The identification of PT in professional basketball players is often difficult because players are used to playing with tendon pain without complaining, for fear of not advancing in competition [ 17 , 18 ]. As such, it is an important challenge to identify the risk of lower limb injury, such as anterior cruciate ligament tear [ 19 ], thigh muscular injuries [ 20 ] and PT.…”
Section: Introductionmentioning
confidence: 99%
“…Two months after surgery, knee range of motion increased to near normal, 0°-90°. And if the correct exercise is performed, there is still a great chance of recovery and even participate in sports activities [32].…”
Section: Discussionmentioning
confidence: 99%